A befogadó közösség, avagy lelkigondozás másként? – Kiselőadás - BERSZÁN, Lídia (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Receptive Community or a Different Kind of Pastoral Care? – Workshop Inclusive attitude can be learned and taught at the same time. We are provided with plenty of chances to acquire it personally, as individuals, particularly in the context of the natural encounters and relationships born out of the everyday realities of our lives. However, it can be learnt as a community as well – how to become a home to those who are “special” in a certain way. As a pastoral care worker, too, taking those internal and external steps leading from compassion to participation is a key learning task of acceptance and inclusion.